Susceptibility Pattern of Tetracycline-Resistant Salmonella Species to other Antibiotics and some Plant Extracts - Asmau Nna Sulaiman; Auwalu Halliru Arzai; Dalha Wada Taura (UMYU Journal of Microbiology Research)
Study’s Excerpt: